Giant ICA Cavernous Aneurysm with Coarctation of Aorta and Autoimmune Hemolytic Disease Posted for Flow Diverter Stenting - Gali, Yagna M.; Bhushanam, Moparthi R.; Gurrala, Shekhar R.; Reddy, Sanna R.; Pathak, Vipul (Journal of Neuroanaesthesiology and Critical Care, 2023)
Anesthetic management of a case of intracranial aneurysm with coarctation of the aorta poses a formidable challenge to the anesthesiologist. The perioperative risks associated with such cases are rupture of an aneurysm, cardiac arrhythmias, stroke from cerebral insufficiency, intracerebral hemorrhage, myocardial ischemia, thromboembolic stroke, and aortic dissection. Endovascular stenting is preferred over surgical clipping of an aneurysm as flow diverter stenting has less morbidity and mortality compared to the latter, and the parent vessel can also be preserved. Despite the perioperative risks, successful stenting of an internal carotid artery aneurysm is beneficial in preventing impending aneurysm rupture and the progressive worsening of neurological symptoms. Therefore, it is imperative to understand the physiological basis behind the unforeseen complex hemodynamic fluctuations occurring during the procedure, as well as the anesthetic goals and complications encountered during the procedure. We describe and discuss the successful anesthetic management of a case of a giant internal carotid artery aneurysm with coarctation of the aorta and autoimmune hemolytic disease posted for flow diverter stenting.
Keywords: internal carotid artery aneurysm; coarctation of aorta; flow diverter stenting; case report